Quantitative and qualitative determination of some components of Syrian mountain honey (Journal of Hama University, 2026)
This study investigated selected physicochemical properties of Syrian mountain honey produced in the Salnfa area, located in the rural countryside of Latakia, during the year 2023. The analytical approach utilized Atomic Absorption Spectrometry (AAS) for the determination of mineral element content. In parallel, standard qualitative chemical tests were employed to detect the presence of various organic compounds, including sugars (such as sucrose, reducing sugars, pentoses, and ketohexoses), amino acids (using Hopkins-Cole, Sakaguchi, Ninhydrin, and Biuret reagents), and vitamins (B2 and D). Additionally, the proline content was quantified via spectrophotometry. The results indicated that potassium was the most abundant mineral, with a concentration of 1220 ppm, followed by sodium at 464.8 ppm. Conversely, the concentrations of copper, zinc, and lead were recorded at 51.91 ppm, 2.056 ppm, and 1.15 ppm, respectively. The qualitative assays yielded positive results, confirming the presence of a diverse range of the tested sugars, amino acids, and vitamins in the honey sample. The quantified proline content was 317.7 mg/kg, a notably high value that is indicative of the honey's maturity and superior quality. In conclusion, these findings substantiate the high nutritional value and confirm the complete maturity of the studied Syrian mountain honey..